Associations Between Cognitive Functioning and Mortality in a Population-Based Sample of Older United States Adults: Differences by Sex and Education. (October 2022) - Adjoian Mezzaca, Tamar; Dodds, Leah V.; Rundek, Tatjana; Zeki Al Hazzouri, Adina; Caunca, Michelle R.; Gomes-Osman, Joyce; Loewenstein, David A.; Schneiderman, Neil; Elfassy, Tali
Objective: To determine whether cognition is associated with mortality among older US adults.Methods: We studied 5, 989 National Health and Nutrition Examination Survey participants age 60+ in years 1999–2014 with mortality follow-up through 2015. Cognitive function was measured in one standard deviation decrements using the Digit Symbol Substitution Test (DSST), Animal Fluency (AnFl), and two Consortium to Establish a Registry for Alzheimer's Disease (CERAD) tests.Results: Each decrement in cognitive function was associated with increased risk of mortality overall (DSST HR: 1.36, 95% CI: 1.25, 1.48), among women only (AnFl: 1.51, 95% CI: 1.02, 2.24), and among those with less than a high school education only (AnFl HR: 1.46, 95% CI: 1.09, 1.97; CERAD-WL HR: 1.34, 95% CI: 1.07, 1.67; and CERAD-DR HR: 1.38, 95% CI: 1.05, 1.82).Discussion: Among US adults, lower cognitive functioning was associated with mortality; associations were stronger among women and those with less education.